Investigating resistance to 5-Azacytidine and Venetoclax in PDX models of MDS/AML - Bašová, Petra; Minařík, Lubomír; Magalhaes-Novais, Silvia Carina; Balounová, Jana; Zemanová, Zuzana; Aghová, Tatiana; Špaček, Martin; Jonášová, Anna; Pimková, Kristýna Gloc; Procházka, Jan; Sedláček, Radislav; Stopka, Tomáš (Frontiers in Oncology, 2025)
IntroductionProgressing myelodysplastic syndrome (MDS) into acute myeloid leukemia (AML) is an indication for hypomethylating therapy (HMA, 5-Azacytidine (AZA)) and a BCL2 inhibitor (Venetoclax, VEN) for intensive chemotherapy ineligible patients. Mouse models that engraft primary AML samples may further advance VEN + AZA resistance research.MethodsWe generated a set of transplantable murine PDX models from MDS/AML patients who developed resistance to VEN + AZA and compared the differences in hematopoiesis of the PDX models with primary bone marrow samples at the genetic level. PDX were created in NSGS mice via intraosseal injection of luciferase-encoding Lentivirus-infected MDS/AML primary cells from patient bone marrow. We validated the resistance of PDX-leukemia to VEN and AZA and further tested candidate agents that inhibit the growth of VEN/AZA-resistant AML.Results and discussionTransplantable PDX models for MDS/AML arise with 31 % frequency. The lower frequency of transplantable PDX models is not related to peritransplant lethality of the graft, but rather to the loss of the ability of short-term proliferation of leukemic progenitors after 10 weeks of engraftment. There exist subtle genetic and cytological changes between primary and PDX-AML samples however, the PDX models retain therapy resistance observed in patients. Based on in vitro testing and in vivo validation in PDX models, Panobinostat and Dinaciclib are very promising candidate agents that overcome dual VEN + AZA resistance.